Unveiling Pakistan’s transport problems: a call to safeguard public health - Habib, Ashna; Ali, Tooba; Nazir, Zainab; Muskan, Fiza; Jawed, Ifra; Akilimali, Aymar (Frontiers in Public Health, 2024)
Public transportation is an important mode of transportation in developing countries like Pakistan since it is accessible and convenient. But there are also serious health hazards associated with it, especially when it comes to the transmission of infectious diseases including COVID-19, TB, and Haemophilus influenzae. Worldwide transportation systems are vulnerable, as the COVID-19 pandemic has shown, underscoring the necessity for study and mitigating measures. The danger of disease transmission is increased in Pakistan by crowded metropolitan areas, inadequate sanitation, and low health awareness. In addition, congested public transportation and inadequate ventilation lead to reduced air quality and elevated stress levels among commuters. Comprehensive actions are needed to address these health hazards, such as promoting physical distance, improving cleanliness, enforcing traffic safety laws, and implementing policy changes that support sustainable transportation. Community involvement and advocacy are critical in campaigning for safer and more sustainable transportation networks. Pakistan can enhance public health outcomes and reduce the health hazards linked to public transportation by giving priority to these measures.